Change in prevalence and severity of metabolic syndrome in the Sami and non-Sami population in rural Northern Norway using a repeated cross-sectional population-based study design: the SAMINOR Study - Michalsen, Vilde Lehne; Kvaløy, Kirsti; Svartberg, Johan; Siri, Susanna Ragnhild; Melhus, Marita; Broderstad, Ann Ragnhild (BMJ Open, 2019)
Objective - To examine the change in both the prevalence and severity of metabolic syndrome (MetS) in the Sami and non-Sami in Northern Norway due to a lack of knowledge regarding the development of MetS in this population. Design - Repeated cross-sectional study. Setting - The study is based on data from the SAMINOR 1 Survey (2003–2004, n=6550) and the SAMINOR 2 Clinical Survey (2012–2014, n=6004), conducted in 10 municipalities in Northern Norway. Participants - Men and women aged 40–79 years were invited. We excluded participants not handing in the questionnaire and with missing information concerning ethnicity questions or MetS risk factors resulting in a final sample of 6308 (36.0% Sami) subjects in SAMINOR 1 and 5866 (40.9% Sami) subjects in SAMINOR 2. Outcome measures - MetS prevalence was determined using the harmonised Adult Treatment Panel III (ATP-III) criteria, and severity was assessed with the MetS severity Z-score. Generalised estimating equations with an interaction term (survey × ethnicity) were used to compare prevalence and severity between the two surveys while accounting for partly repeated measurements. Results - The overall, age-standardised ATP-III-MetS prevalence was 31.2% (95% CI: 29.8 to 32.6) in SAMINOR 1 and 35.6% (95% CI: 34.0 to 37.3) in SAMINOR 2. Both the ATP-III-MetS prevalence and the mean MetS severity Z-score increased between the surveys in all subgroups, except the ATP-III-MetS prevalence in non-Sami women, which remained stable. Over time, Sami men showed a slightly larger increase in MetS severity than non-Sami men (p<0.001): the score increased by 0.20 (95% CI: 0.14 to 0.25) and 0.06 (95% CI: 0.01 to 0.10) in Sami and non-Sami men, respectively. Abdominal obesity increased markedly between the surveys in all subgroups. Conclusion - The prevalence and severity of MetS increased over time in rural Northern Norway. Abdominal obesity appeared to drive the increase in ATP-III-MetS prevalence. Sami men had a slightly larger increase in severity than non-Sami.